2009
DOI: 10.1016/j.diagmicrobio.2009.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular epidemiology of methicillin-resistant Staphylococcus aureus carrying SCCmecIV in a university hospital in Porto Alegre, Brazil

Abstract: We evaluated clinical outcomes and molecular epidemiology of methicillin-resistant Staphylococcus aureus carrying SCCmecIV recovered from patients who attended at a teaching hospital from Porto Alegre, Brazil. All Panton-Valentine leukocidin (PVL)-producer isolates belonged to clonal complex (CC) 30 (11 isolates, related to Oceania Southwest Pacific clone [OSPC]), and the PVL-negative isolates were typed as CC5 (2 isolates, related to the pediatric clone). Five patients had health care-associated infections (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Our study found no MRSA nasal carriage among patients attended to a PHU from Porto Alegre, a Brazilian city where the first CA-MRSA has been described in South America and where most cases of CA-MRSA have been described so far 11 . This result may be partially explained by the fact that we did not assess children, a population with higher rates of MRSA colonization 13 .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Our study found no MRSA nasal carriage among patients attended to a PHU from Porto Alegre, a Brazilian city where the first CA-MRSA has been described in South America and where most cases of CA-MRSA have been described so far 11 . This result may be partially explained by the fact that we did not assess children, a population with higher rates of MRSA colonization 13 .…”
Section: Discussionmentioning
confidence: 83%
“…Prevention of staphylococcal infections and reduction of the spread of CA-MRSA are of great importance 12 . Thus, the objective of this report was to assess the prevalence of MRSA nasal carriage among individuals consulting at a primary-healthcare unit (PHU) in Porto Alegre, Brazil, where most cases of CA-MRSA from Brazil have been reported so far 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In Latin-American countries, specially Argentina and Brazil, other authors have reported the presence of PVLproducer and non-producer MRSA strains carrying SCCmec IV, which cause both community and health-care associated infections (mainly severe SSTI, bacteraemia, osteomyelitis and pneumonia or chronic lung infection) and colonise healthy adults and children (Trindade et al 2005, de Miranda et al 2007, Rozenbaum et al 2009, Scribel et al 2009, Gardella et al 2011, Mimica et al 2011. Nevertheless, there is little information available about the virulence factors present in the isolates and most studies do not include SCCmec typing or any molecular characterisation of the strains.…”
Section: Discussionmentioning
confidence: 99%
“…These SCCmec types were also detected in MRSA surveys conducted in different Brazilian hospitals. However, the prevalence of SCCmec types varied between different regions [3,[25][26][27][28][29][30][31]. The Brazilian epidemic clone (BEC) carrying the SCCmec type III has been the predominant clone in several hospitals in Brazil [28,29,32].…”
Section: Discussionmentioning
confidence: 99%